Comparative Cost-Effectiveness of Clinic, Home, or Ambulatory Blood Pressure Measurement for Hypertension Diagnosis in US Adults: A Modeling Study. Issue 1 (January 2019) - Beyhaghi, Hadi; Viera, Anthony J.
Abstract : Previous cost-effectiveness models found ambulatory blood pressure monitoring (ABPM) to be a favorable strategy to diagnose hypertension; however, they mostly focused on older adults with a positive clinic blood pressure (BP) screen. We evaluated the cost-effectiveness of 3 methods of BP measurement for hypertension diagnosis in primary care settings among 14 age- and sex-stratified hypothetical cohorts (adults ≥21 years of age), accounting for the possibility of both false-positive (white-coat hypertension) and false-negative (masked hypertension) clinic measurements. We compared quality-adjusted life-years and lifetime costs (US 2017 from the US healthcare perspective) associated with clinic BP measurement, home BP monitoring, and ABPM under 2 scenarios: positive and negative initial screen. Model parameters were obtained from published literature, publicly available data sources, and expert input. In the screen-positive scenario, ABPM was the dominant strategy among all age and sex groups. Compared with clinic BP measurement, ABPM was associated with cost-savings ranging from 77 (women 80 years of age) to 5013 (women 21 years of age). In the screen-negative scenario, ABPM was the dominant strategy in all men and women <80 years of age with cost-savings ranging from 128 (women 70 years of age) to 2794 (women 21 years of age). Sensitivity analyses showed that results were sensitive to test specificity and antihypertensive medication costs. ABPM is recommended as the diagnostic strategy of choice for most adults in primary care settings regardless of initial screening results.